EPCO-08. TUMOR-IMMUNE INTERACTIONS ARE DYNAMIC AND INFLUENCE THE EVOLUTIONARY TRAJECTORY OF ADULT DIFFUSE GLIOMA. (9th November 2020) - Varn, Frederick; Johnson, Kevin; Barthel, Floris; Kim, Hoon; Wade, Taylor; Lodha, Disha; Ajaib, Shoaib; Ahmed, Nazia; Garofano, Luciano; D'Angelo, Fulvio; Stead, Lucy; Noushmehr, Houtan; et al.
Abstract: Diffuse glioma is an aggressive brain cancer that is characterized by a poor prognosis and a universal resistance to therapy. The evolutionary processes behind this resistance remain unclear. Previous studies by the Glioma Longitudinal Analysis (GLASS) Consortium have indicated that therapy-induced selective pressures shape the genetic evolution of glioma in a stochastic manner. However, single cell studies have revealed that malignant glioma cells are highly plastic, and capable of changing their cell state in response to diverse challenges in their microenvironment. The tumor immune response has been implicated as a major driver of these malignant cell state transitions, and is known to be affected by the administration of therapy, but the extent to which tumor genetics, therapy, and the different components of the immune response interact to influence a glioma's evolutionary trajectory are poorly understood. To further investigate these factors, we collected DNA and RNA sequencing data on pre- and post-treatment tumor pairs from over 150 glioma patients that have received chemotherapy, radiotherapy, and/or immune checkpoint blockade agents. By integrating mutation, copy number, and in silico deconvolution analyses of bulk transcriptome data across the three molecular subtypes of diffuse glioma, we show that longitudinal increases in chromosomal instability and gene fusions associate with decreased immune infiltrate and altered cell states at recurrence. We additionally find that specific molecular alterations and malignant cell states associate with unique inflammatory and immunosuppressive programs in tumor-associated macrophages and microglia. Lastly, we show that the abundance of T cells in the tumor microenvironment does not associate with changes in neoantigen depletion and the acquisition of antigen presentation machinery defects, suggesting minimal immunoediting activity over time. Collectively, our results indicate that the administration of therapy can alter the dynamics of tumor-immune interactions in glioma, resulting in new steady-states at recurrence that can be subsequently targeted.